Prediction of harmful variants on mitochondrial genes: Test of habitat-dependent and demographic effects in a euryhaline fish - Vasemägi Anti; Sulku Janne; Bruneaux Matthieu; Thalmann Olaf; Mäkinen Hannu; Ozerov Mikhail (WILEY, 2022)
Both effective population size and life history may influence the efficacy of purifying selection, but it remains unclear if the environment affects the accumulation of weakly deleterious nonsynonymous polymorphisms. We hypothesize that the reduced energetic cost of osmoregulation in brackish water habitat may cause relaxation of selective constraints at mitochondrial oxidative phosphorylation (OXPHOS) genes. To test this hypothesis, we analyzed 57 complete mitochondrial genomes of Pungitius pungitius collected from brackish and freshwater habitats. Based on inter- and intraspecific comparisons, we estimated that 84% and 68% of the nonsynonymous polymorphisms in the freshwater and brackish water populations, respectively, are weakly or moderately deleterious. Using in silico prediction tools (MutPred, SNAP2), we subsequently identified nonsynonymous polymorphisms with potentially harmful effect. Both prediction methods indicated that the functional effects of the fixed nonsynonymous substitutions between nine- and three-spined stickleback were weaker than for polymorphisms within species, indicating that harmful nonsynonymous polymorphisms within populations rarely become fixed between species. No significant differences in mean estimated functional effects were identified between freshwater and brackish water nine-spined stickleback to support the hypothesis that reduced osmoregulatory energy demand in the brackish water environment reduces the strength of purifying selection at OXPHOS genes. Instead, elevated frequency of nonsynonymous polymorphisms in the freshwater environment (P-n/P-s=0.549 vs. 0.283; Fisher's exact test p=.032) suggested that purifying selection is less efficient in small freshwater populations. This study shows the utility of in silico functional prediction tools in population genetic and evolutionary research in a nonmammalian vertebrate and demonstrates that mitochondrial energy production genes represent a promising system to characterize the demographic, life history and potential habitat-dependent effects of segregating amino acid variants.